Spathiphyllum Flowering – Keys to the Future - Richard J. Henny; Jianjun Chen (EDIS, 2007)
ENH-1047, a 2-page fact sheet by R.J. Henny and J. Chen, describes flowering induction research that explores the potential use of environmental manipulation instead of gibberillic acid sprays to time flowering in peace lilies. Published by the UF Department of Environmental Horticulture, November 2006.